PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA WOM (WORD OF MOUTH) (SURVEY PADA PELANGGAN OJEK ONLINE MAXIM DI KOTA PONTIANAK) - Steven Steven (Jurnal Ekonomi Integra, 2020)
Brand image, price, and good customer value, of course, have an impact on customer satisfaction. If the customer is satisfied with the services or products provided, of course, will recommend services and products purchased or used will create positive Wom. This study wants to prove the effect of each variable is brand image, price perception, customer value, and customer satisfaction as an intervening variable to Wom users of Maxim online transportation services in Pontianak. Based on previous research and linked to supporting theories put forward by experts using SPSS as a statistical data processing device. This type of research is associative research. In this study, researchers used a nonprobability sampling technique because the researcher did not know the total number of members of the population under study. While the sampling technique used in this study was accidental sampling. Whereas the sample population numbered 100 people, with data analysis techniques using Path Analysis. Based on data processing using path analysis, it is evident that brand image, price perception, customer value affect customer satisfaction, and customer satisfaction also has a positive and significant effect on Wom with customer satisfaction as an intervening variable.